Adjoining a Constant Function to n-Dimensional Chebyshev Space. (17th August 2016) - Alyazidi-Asiry, Mansour
Abstract : This paper is concerned with extending a Chebyshev system of n continuous nonconstant functions into a set of n + 1 functions including a constant function. Necessary and sufficient conditions for the new set to be a Chebyshev system are discussed and some results are obtained.